The prophenoloxidase system and in vitro interaction of Trypanosoma rangeli with Rhodnius prolixus and Triatoma infestans haemolymph - Gregório, E. A. [UNESP]; Ratcliffe, N. A. (Parasite Immunology, 1991)
The presence of the prophenoloxidase (proPO) system in the haemolymph of Rhodnius prolixus and Triatoma infestans and the role played by Trypanosoma rangeli in the in vitro activation of proPO were tested. Both R. prolixus and T. infestans whole blood preparations showed a very active ProPO system. The proPO cascade of the two insect species were differentially activated by microbial-derived extracts: laminarin was a better activator of T. infestans haemolymph than of R. prolixus blood, and lipopolysaccharides from Shigella flexneri or Pseudomonas aeroginosa caused significant proPO activation of T. infestans haemolymph but not of R. prolixus preparations. For the two insect species, neither T. rangeli from culture nor parasite lysates were able to trigger proPO activation. The presence of the parasite in R. prolixus haemolymph/laminarin assays, however, significantly reduced the level of proPO activation to that of spontaneous activating controls. The immobilization of T. rangeli in vitro in haemolymph preparations occurred in both insect species and was dependent on the proPO activation intensity. Our results suggest that the susceptibility of R. prolixus to T. rangeli haemocoel infection may be explained, at least in part, by the suppression of the insect immune defence system i.e., inhibition of proPO in the presence of this protozoan parasite.